PEMBERIAN JAMBU BIJI MERAH TERHADAP PENINGKATAN KADAR HEMOGLOBIN PADA IBU HAMIL - Asiah, Asiah; Utami, Risqi (Zona Kebidanan: Program Studi Kebidanan Universitas Batam, 2024)
Anemia in pregnancy is a condition with hemoglobin (Hb) levels < 11gr% in the first and third trimesters while the hemoglobin level in the second trimester is < 10.5gr%. Untreated anemia in pregnant women will result in suboptimal growth and development of the fetus in the womb and has the potential to cause complications in pregnancy and childbirth, even causing maternal death. Prevention and treatment of iron deficiency anemia can be done by consuming blood supplement (Fe) tablets per day and adding vitamin C. Red guava is a fruit rich in vitamin C. The vitamin C contained in guava increases the absorption of iron by the body, so that the body can absorb iron optimally. The aim of this care is to provide care to anemic pregnant women by giving them red guava juice to increase hemoglobin levels. This research method is a type of descriptive research with a case study approach. The sample was 1 pregnant woman G1P0A0 UK 36 weeks with mild anemia. The care provided is by administering 1 x 250 ml of red guava juice per day for 7 days from 15 – 21 March 2024. Care is carried out in 2 visits. From 7 days of care, the result was an increase in the mother's hemoglobin level of 1.8 gr/dl, where previously the mother's first Hb was 10.7 gr/dl to 12.5 gr/dl. It was concluded that giving red guava juice can increase hemoglobin levels in anemic pregnant women.